Food Defense Planning and Implementation in a Food Ingredients Manufacturing Facility - Saathoff, Scott (My University, 2011)
The Food Safety Modernization Act (FSMA) of 2011 explicitly and implicitly charges the food industry with the responsibility of protecting food supply chains against intentional contamination. This field experience was conducted at a global food ingredients manufacturing facility located in the Midwestern United States. The field experience aimed at increasing the food defense readiness of the facility to a level more consistent with the mandates promulgated by FSMA. A food defense audit was conducted to assess the food defense vulnerabilities present at the facility. Vulnerabilities were assessed relating to (1) food defense plan management, (2) outside security, (3) inside security, and (4) personnel security relating to the facility. The food defense audit provided recommendations to mitigate any identified vulnerabilities; additionally, strategies were proposed to implement those recommendations. A brief overview is given of the recommendations that were either approved for immediate implementation or were placed under review for possible, future implementation. Finally, a working document was written that will serve as the official food defense plan of the facility. The food defense plan is a confidential document that contains information about the pertinent physical and geographical characteristics of the facility, contact information for local law enforcement, fire departments, Federal Bureau of Investigation (FBI), state and national homeland security departments, and other important contact information. The plan briefly discusses the food defense audit results, and gives an overview of the security procedures for the management of the food defense plan, outside security, inside security, and personnel security. At the request of the company, this document was created as a working document, so some sections were left incomplete and will be completed at a later date by the company as decisions about procedures and personnel are made. Due to the confidential nature of the food defense plan, this field experience report contains a summary of the plan.
Keywords: Food defense; Manufacturing facility; FSMA 2011; Global food ingredient manufacturing; Public Health (0573)